Femtosecond Laser Ablated Polymer SERS Fiber Probe With Photoreduced Deposition of Silver Nanoparticles - Geng Youfu; Yin Zhen; Tan Xiaoling; Du Yu; Hong Xueming; Li Xuejin (IEEE Photonics Journal, 2016)
In this paper, a surface-enhanced Raman scattering (SERS) spectral probe based on a polymethylmethacrylate (PMMA) polymer fiber is produced by femtosecond laser ablation and photoreduced deposition of silver nanoparticles. It shows that a surface grating structure enabled by femtosecond laser ablation could further improve the SERS signal by around four times larger than the ordinarily roughened structure. By varying femtosecond laser pulse energy and scan surface period in the fabrication process, the enhancement factor of the SERS signal is optimized with laser scan surface period of around 5 μm at 1.2 μJ femtosecond laser pulse energy for a PMMA fiber probe. In particular biochemical analysis, much softer SERS probes are preferred, and our polymer SERS fiber probe shows an alternative method for in situ measurement of the SERS signal and further fabrication of polymer SERS microchip.